ESTABLISHING MEASUREMENT INVARIANCE ACROSS ONLINE AND OFFLINE SAMPLES. A TUTORIAL WITH THE SOFTWARE PACKAGES AMOS AND MPLUS - Cieciuch, JAN; DAVIDOV, ELDAD (Studia Psychologica: Theoria et praxis, 2015)
Establishing measurement invariance for indicators measured using online and offline modes of data collection is a precondition for the comparison of such data. Furthermore, it may allow accumulating knowledge using data from different sources or pooling data collected using different methods. The main goal of the current paper is to present a tutorial outlining the procedure of testing for measurement invariance using the Amos and Mplus software packages. We focus on the following steps for performing a measurement invariance test: 1) model specification, 2) model identification, 3) modelestimation and evaluation, and 4) model modification.